Brazing and magnetic properties control of sintered NdFeB permanent magnet with high coercivity. (December 2022) - Xv, Wentao; Wang, Shaofeng; Cai, Liping; Zhang, Xinyang; Dou, Zhanguo; Luo, Wei
Abstract: This article presents an application of vacuum brazing to join sintered NdFeB permanent magnet N33UH with high coercivity. The magnets were effectively brazed with BCu91AgP Cu-based brazing filler metal at 680°C. The shear strength of the joint was up to 113.19 MPa. Meanwhile, the principal magnetic properties decreased. Subsequently heat treatment for 3 hours at 460-550°C could notably improve magnetic properties. This increase in magnetic properties was mainly attributed to the formation of continuous thin Nd-rich grain boundary phases between the main phases. Heat treated at 520°C, Br, HcB, HcJ, and (BH)max reached 95.4%, 95.9%, 99.8% and 91.4% of as-received magnet, respectively. Graphical abstract: Image, graphical abstract